Comparison of Attachment Styles in Adolescents and Adults with Obsessive and Non-Obsessive Mothers - Sattari, Fahimeh; Azizi, Morteza (Iranian Journal of Neurodevelopmental Disorders, 2026)
Purpose: The present study aimed to compare attachment styles in adolescents and adults with obsessive and non-obsessive mothers. Methods and Materials: This study employed a causal-comparative (ex post facto) research design. The statistical population consisted of all individuals aged 14 to 40 years residing in District 4 of Tabriz in 2026 whose mothers had referred to psychological centers and clinics due to obsessive behaviors; the population size was reported as 2,736 individuals. The sample size was determined using Cochran’s formula, and ultimately 340 participants were selected through convenience sampling. The research instruments included the Attachment Styles Questionnaire Hazan & Shaver, 1987. Data were analyzed using multivariate analysis of variance through SPSS version 27, and the significance level for the tests was set at 0.05. Findings The findings indicated significant differences in attachment styles between adolescents and adults with obsessive mothers and those with non-obsessive mothers (p < .05). Specifically, children of obsessive mothers obtained higher scores on anxious and avoidant insecure attachment styles and lower scores on secure attachment style (p < .05). Conclusion: Based on the findings, it can be concluded that parental characteristics and interactions within families affected by obsessive behaviors may contribute to the development of maladaptive cognitive-emotional patterns in children. Accordingly, the necessity of designing preventive interventions and empowering children from such families to enhance coping skills and reduce negative psychological consequences is emphasized.